Optimization Yield and Physical Characteristics of Household-Scale Coconut Oil through Various Simple Extraction Methods - Rasmiyana Rasmiyana; Angga Prasetyo (Jurnal Biologi Tropis, 2026)
The selection of coconut oil extraction methods at the household scale needs to consider the quality and quantity of the resulting product. This study aimed to optimize simple coconut oil extraction methods based on physical characteristics, organoleptic properties, yield, and water content. A Completely Randomized Design (RAL) was used with 4 treatment methods: P1 (dry method/direct heating of grated coconut), P2 (wet method with direct heating of coconut milk), P3 (wet method with the addition of 1% papain enzyme), and P4 (wet method with separation of skim and cream from coconut milk). Test parameters included organoleptic tests (color, aroma, taste), yield, and water content. The results showed that the extraction method significantly affected yield and water content but did not significantly affect panelists preference for color. The dry method (P1) produced the highest yield (14.77%) but had the lowest organoleptic quality. The wet methods with skim-cream separation and papain enzyme addition (P3) produced the best organoleptic quality with the lowest water content (0.17%). SNI standard of water content maximum 0.5%. In conclusion, the wet extraction method with skim-cream separation and the addition of proteolytic enzymes such as papain is recommended for household-scale production as it produces superior quality oil with low water content.